Arterial stiffness and endothelial function in the long-term period after a coronavirus disease 2019 - S. A. Bondar; O. P. Rotar; E. V. Moguchaya; M. А. Boyarinova; E. P. Kolesova; E. Yu. Vasilyeva; A. A. Mikhailova; T. L. Karonova; A. O. Konradi (Российский кардиологический журнал)
Aim. To assess endothelial function and arterial stiffness over time in patients after hospitalization with coronavirus disease 2019 (COVID-19) and compare them with a control group.Material and methods. A total of 53 patients over 18 years of age were hospitalized for COVID-19 in June — August 2021 was examined at two visits: the first — 10-16 months, the second — 14-23 months after discharge from the hospital. Control group included 53 patients from the ESSE-RF epidemiological study of a St. Petersburg population who did not have COVID-19, selected by sex, status of smoking, hypertension and type 2 diabetes. Endothelial function was assessed by the levels of vascular cell adhesion molecule 1 (VCAM-1) and von Willebrand factor (vWF) in plasma and the reactive hyperemia index (lnRHI) on the EndoPAT 2000 system. Carotid-femoral pulse wave velocity (cfPWV) was determined using the SphygmoCor device, while cardio-ankle vascular index (CAVI) and ankle-brachial index (ABI) — using the VaSera device.Results. The prevalence of endothelial vasomotor function disorders at the first and second visits in the active group did not differ significantly as follows: lnRHI £0,51 — 21% and 21%, cfPWV >10 m/s — 17% and 14%, and SLSI >9 — 28% and 34%, respectively. Plasma VCAM-1 levels were significantly higher during hospitalization than at the first and second visits — no differences were found between visits. The levels of lnRHI, vWF, cfPWV, CAVI, ABI at the first and second visits did not differ significantly. Post-COVID-19 patients differed from the control group only by a significantly higher ABI level at the second visit. According to the analysis of covariance, COVID-19 is associated with a CAVI increase at the first visit, as well as with an increase in ABI at both visits.Conclusion. The 1,5-2-year follow-up of patients after COVID-19, which required hospitalization, showed a decrease in the plasma endothelial dysfunction parameter VCAM-1. There is no changes in endothelial function and arterial stiffness over a period of time from 10-16 months to 14-23 months after hospitalization with COVID-19.